Las empresas fantasmas y la evasión tributaria en Ecuador, período 2020 – 2023 - Lozano Mosquera, Quely Xiomara (2025)
The document titled "Ghost Companies and Tax Evasion" addresses the issue of fictitious companies and their impact on tax collection in Ecuador. The research analyzes how these entities, which operate without economic activity, contribute to tax evasion by declaring non-existent expenses and engaging in other fraudulent practices. Additionally, the study examines the evolution of tax reforms in the country. Between 2020 and 2023, 1,074 ghost companies were identified, generating transactions amounting to $70.05 million. These operations involved 22,141 clients across several provinces, including Guayas, Pichincha, El Oro, Manabí, Azuay, and Santo Domingo de los Tsáchilas. The tax evasion rate in Pichincha was 18.69%, while in Guayas, it reached 10.41%. These figures are higher than the national average of 9.00% related to Income Tax. The study concludes by recommending enhanced controls and supervision by the SRI (Tax Administration Service) in collaboration with the Superintendency of Companies and the Commercial Registry. This cooperation is essential to identify and eliminate these fraudulent companies. Furthermore, it suggests promoting a more incredible tax culture through educational campaigns and ongoing monitoring to reduce tax evasion, which was identified in this study at a rate of 49.20%.